2019
DOI: 10.1007/s13205-019-1608-9
|View full text |Cite
|
Sign up to set email alerts
|

An optimized method to obtain high-quality RNA from cassava storage root

Abstract: Extracting RNA with high quality and integrity is crucial for molecular biology studies in eukaryotes. However, RNA isolation from cassava storage root raises a great concern because it contains large amounts of polysaccharides and polyphenol compounds. In the current study, four RNA extraction methods were evaluated for extracting RNA from cassava storage root. We found that the modified TM method (MTM) is timesaving and low-cost extraction method with high quality and quantities of RNA. The effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In the present study, we obtained RIN≥ 6.6 for the RNA samples obtained through the three RNA isolation methods tested (Figure 3), what is similar to other studies present in the literature, such as transcriptional studies through qPCR from Coffea arabica (Freitas et al, 2017), Pelargonium zonale, and Ramonda serbica (Vidović and Ćuković, 2020), and Manihot esculenta (Behnam et al, 2019;Guan et al, 2019). For instance, in the study developed by Freitas et al (2017), RINs ≥ 7.0 were obtained for different tissues in an assay for the validation of reference genes for RT-qPCR analysis of Coffea arabica somatic embryogenesis-related tissues.…”
Section: Rna Integritysupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we obtained RIN≥ 6.6 for the RNA samples obtained through the three RNA isolation methods tested (Figure 3), what is similar to other studies present in the literature, such as transcriptional studies through qPCR from Coffea arabica (Freitas et al, 2017), Pelargonium zonale, and Ramonda serbica (Vidović and Ćuković, 2020), and Manihot esculenta (Behnam et al, 2019;Guan et al, 2019). For instance, in the study developed by Freitas et al (2017), RINs ≥ 7.0 were obtained for different tissues in an assay for the validation of reference genes for RT-qPCR analysis of Coffea arabica somatic embryogenesis-related tissues.…”
Section: Rna Integritysupporting
confidence: 88%
“…In relation to the TRIzol method, though it is widely used in transcriptional studies of sweet potato (Figure 1), the results found in this study were not satisfactory. Although this RNA extraction method has been used in other species (Acosta-Maspons et al, 2019;Behnam et al, 2019;Guan et al, 2019), the different optimizations present in these studies were not sufficient to improve the purity of RNA obtained.…”
Section: Rna Quantity and Puritymentioning
confidence: 98%
“…However, extracting high-quality RNA samples from Lilium bulbs is a tough process as polysaccharides and polyphenols tend to co-precipitate with RNA [21,22]. The composition of plant tissues varies greatly, which requires different approaches to obtain high-quality RNA [23,24]. Several RNA extraction methods have been reported in Pistachio [25], Cassava [23], Sun ower [26], sugar beet [27] and Jerusalem artichoke seeds [21], but it may not suitable for Lilium davidii var.…”
Section: Discussionmentioning
confidence: 99%
“…The reported traditional TRIzol method is not suitable for obtaining high-quality RNA from cassava storage roots [23]. Meanwhile, we initially tried to extract RNA samples from different tissues of Lilium by applying modi ed CTAB method and Kit approaches, but the results remained unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation